An Activity‐Based Ratiometric Fluorescent Probe for In Vivo Real‐Time Imaging of Hydrogen Molecules. Issue 9 (14th January 2022) - Gong, Wanjun; Jiang, Lingdong; Zhu, Yanxia; Jiang, Mengna; Chen, Danyang; Jin, Zhaokui; Qin, Shucun; Yu, Zhiqiang; He, Qianjun
Abstract: To reveal the biomedical effects and mechanisms of hydrogen molecules urgently needs hydrogen molecular imaging probes as an imperative tool, but the development of these probes is extremely challenging. A catalytic hydrogenation strategy is proposed to design and synthesize a ratiometric fluorescent probe by encapsulating Pd nanoparticles and conjugating azido‐/coumarin‐modified fluorophore into mesoporous silica nanoparticles, realizing in vitro and in vivo fluorescence imaging of hydrogen molecules. The developed hydrogen probe exhibits high sensitivity, rapid responsivity, high selectivity and low detection limit, enabling rapid and real‐time detection of hydrogen molecules both in cells and in the body of animal and plant. By application of the developed fluorescent probe, we have directly observed the super‐high transmembrane and ultrafast transport abilities of hydrogen molecules in cells, animals and plants, and discovered in vivo high diffusion of hydrogen molecules. Abstract : A ratiometric fluorescent hydrogen probe was developed for the first time by a catalytic hydrogenation strategy, enabling efficient detection of hydrogen molecules in vivo and in vitro with high sensitivity, rapid responsivity, high selectivity and low detection limit, in favor of uncovering and understanding underlying biological behaviors and mechanisms of hydrogen molecules.